PERANCANGAN PIRANTI LUNAK RESPONSIVE UNTUK MONITORING RUANGAN SERVER MENGUNAKAN NODEMCU ESP8266 BERBASIS INTERNET OF THINGS - M. Safii; Novi Indrayani (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2020)
The role of the server is very important as a data service provider and control for an office that has a very large data usage and control system. This can also affect the temperature in the server room which has computer devices and other control systems because of its continuous use. The impact of temperature that is outside of its tolerance value due to the dead air conditioner without being noticed by the officer or server operator can result in damage to the hardware devices in the server room. Monitoring and measuring server room temperature is not possible to be done directly and accurately in all conditions due to several inhibiting factors in obtaining temperature information. With these problems, a temperature monitoring prototype was built using node MCU ESP 2866 and DHT 21 sensor with responsive web-based software so that it can be easily seen on various PC and smartphone monitors. This software can be used in server rooms to provide room temperature information to operators or server officers. The long-term objective of this research is expected to provide information Real-time temperature conditions in a responsive web-based server room.